Due diligence on conservation organisations: what should we be asking? - Sanders, M (2019)
This inductive study explores what criteria could be used to identify conservation organisations more likely to achieve their goals. In addition to information gathered from the academic and grey literature, primary data was obtained from three main sources: semi-structured interviews with 74 conservation practitioners; an online survey completed by 154 conservation practitioners; and review of 35 non-profit organisational effectiveness frameworks. Interviews identified barriers to conservation success, allowing a typology of barriers to be developed. Risks to success can be internal (arising inside an organisation), external (completely outside of an organisation’s control) or operational (outside of individual organisational control, but within the control of the conservation community). Because the list was long, statistical procedures were applied to the survey data to reduce the number of barriers needed to understand operating context. The framework review and survey explored organisational deficiencies that might present internal barriers to effectiveness. I found four dimensions to an effective organisation: governance; finance; leadership; and management. There was less agreement as to which criteria are present in effective organisations. Differences between frameworks used to guide effectiveness and those used to judge it were noted and discussed. Finally, survey results were compared to framework review results to compare viewpoints on effectiveness criteria. Ranked lists were not significantly different, but correlation between them was weak. This study provides the first empirically based conceptual model of barriers to conservation as perceived by conservation practitioners, and a first attempt to identify which barriers, internal and external, may be most important in identifying more effective conservation organisations. My findings also suggest that current criteria applied in funding decisions might be counter-productive: insisting on the presence of unproven effectiveness criteria stretches already pressurised conservation organisations even further and hampers their effectiveness. Instead, the donors could collaborate more and work towards less onerous and untested methods of decision- making.